Horace's Ars poetica : family, friendship, and the art of living - Ferriss-Hill, Jennifer, 1979- (Princeton University Press, 2019)
"Horace's Ars Poetica: Family, Friendship and the Art of Living considers the Ars Poetica (Art of Poetry) as a coherent, complete, and exceptional literary artefact in its own right, and one that occupies a key place in Horace's oeuvre. This 476-line poem has stood for two millennia alongside Aristotle's Poetics as a canonical work of literary theory, taken largely as what it professes itself to be: a handbook, written under commission, for how to write drama. Ferriss-Hill argues that it should rather be read in the context of Horace's other hexameter writings and in particular as a companion and counterpart to his Satires. Just as throughout the Satires, his earliest poems, Horace encodes literary prescriptions into his advice on how to live well, so she contends that the Ars Poetica, thought to be his final work, may be read as a manual for how to live that masquerades as a treatise on poetics. She traces key themes from the poem's opening vignette through its entire length to show that Horace's concerns extend beyond poetry to encompass friendship, laughter, and criticism, intergenerational relationships and life-cycles, and human endeavor broadly conceived. If the poem is read for how it expresses itself, moreover, rather than merely for what it says, it emerges as an ideal exemplum of art in which judicious repetitions of words and ideas fasten the poem's disparate parts together, and the whole proves seamless yet lends itself to being remade in new ways by every reader and upon every reading"--